Mitigation of Learning Loss and Teacher Awareness: Qualitative Study in Science Practicum - Mariana Rengkuan; Fajryani Simal; Marleny Leasa; Marni Maelan (Postgraduate, University of Mataram, 2022)
This study aimed to determine teacher awareness in mitigating learning loss in science practice learning in elementary schools. The research method used was qualitative research with case studies. Data collection techniques used include interviews, observation, and documentation. The research was conducted in elementary schools in Ambon City, consisting of three public and three private schools, with the respondents being high school teachers. In this study, the validity of the triangulation data was used. The results showed that teachers' awareness of mitigating learning loss in science practice in elementary schools was good. However, both public and private schools experienced learning loss in science practice. For this reason, each teacher gives their best effort to mitigate learning loss events by taking actions such as home visits, communicating with parents, utilizing existing media in the environment around students for science practice, and approaching students to mitigate learning loss events in students' science practice in elementary school